2020
DOI: 10.1177/2158244020982993
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Job Insecurity on Employees’ Financial Well-Being and Work Satisfaction Among Chinese Pink-Collar Workers

Abstract: This article examines the effects of job insecurity on employees’ financial well-being and work satisfaction. Based on a literature review on financial well-being, we proposed that financial well-being consists of two categories: personal financial well-being and family financial well-being. We developed a theoretical model that links job insecurity to employees’ personal and family financial well-being, and then to employees’ work satisfaction. Data were collected from 334 Chinese pink-collar workers in Macao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The third thematic area relates to the links of financial well-being with major macroeconomic indicators such as the economic growth of nations (Hampson et al, 2018). Also, recent research has focused on individual life stages and negative events (Chatterjee et al, 2019; Sharma, 2015) and organizational consequences (To et al, 2020) which are the other two thematic areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third thematic area relates to the links of financial well-being with major macroeconomic indicators such as the economic growth of nations (Hampson et al, 2018). Also, recent research has focused on individual life stages and negative events (Chatterjee et al, 2019; Sharma, 2015) and organizational consequences (To et al, 2020) which are the other two thematic areas.…”
Section: Discussionmentioning
confidence: 99%
“…By developing a theoretical model, Choi et al (2020) confirmed that job insecurity leading to lower levels of financial well-being is a major source of stress among individuals and employees. Similarly, poor levels of financial well-being have been connected with lower levels of work satisfaction (To et al, 2020). They also support Prawitz et al ’s (2006) remark that financial stress negatively influences employee productivity.…”
Section: Thematic Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above-discussed studies, financial well-being has also been examined as a mediator by several researchers including Shim et al . (2009) and To et al . (2020).…”
Section: Review Findingsmentioning
confidence: 96%
“…(2009) reported that the financial well-being of young adults mediates the relationship between socializing agents and personal values and life success. On the other hand, To et al . (2020) demonstrated that both employees, as well as family's financial well-being, mediate the relationship between job insecurity and work satisfaction among Chinese pink-collar employees.…”
Section: Review Findingsmentioning
confidence: 98%